2023
DOI: 10.1093/jrsssc/qlad009
|View full text |Cite
|
Sign up to set email alerts
|

Missing data patterns in runners’ careers: do they matter?

Abstract: Predicting the future performance of young runners is an important research issue in experimental sports science and performance analysis. We analyse a dataset with annual seasonal best performances of male middle distance runners for a period of 14 years and provide a modelling framework that accounts for both the fact that each runner has typically run in 3 distance events (800, 1,500, and 5,000 m) and the presence of periods of no running activities. We propose a latent class matrix-variate state space mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recently, researchers have noticed the benefits of accounting for missing data in modeling performance in sports. Stival et al (2023) used a latent class matrixvariate state-space framework to analyze runners' careers, and found that missing data patterns greatly contribute to the prediction of performance. Perhaps the most closely related approach to our work is that by Schuckers et al (2023), which considered different regression and imputation frameworks for estimating the aging curves in the National Hockey League (NHL).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, researchers have noticed the benefits of accounting for missing data in modeling performance in sports. Stival et al (2023) used a latent class matrixvariate state-space framework to analyze runners' careers, and found that missing data patterns greatly contribute to the prediction of performance. Perhaps the most closely related approach to our work is that by Schuckers et al (2023), which considered different regression and imputation frameworks for estimating the aging curves in the National Hockey League (NHL).…”
Section: Literature Reviewmentioning
confidence: 99%